2021
DOI: 10.3390/diagnostics11050863
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Molecular Imaging in a Muscle-Invasive Bladder Cancer Patient: A Narrative Review in the Era of Multimodality Treatment

Abstract: Diagnostic imaging in bladder cancer plays an important role since it is needed from pretreatment staging to follow-up, but a morphological evaluation performed with both CT and MRI showed low sensitivities and specificities in detecting pathologic lymph nodes, due to the occurrence of false positive results. Implementation of functional information provided by PET/CT could be a determinant in the management of patients with muscle-invasive bladder cancer. A focus on the role of 18F-FDG PET/CT and alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…Although the cost of nanocolloids has been decreasing over time, it remains relatively high. The cost of new radiotracers is a major disadvantage of these, considering that the gain in detection rate is not much higher than that obtained with radiocolloids [ 71 ].…”
Section: Advantages and Disadvantages Of Nuclear And Non-nuclear Methodsmentioning
confidence: 99%
“…Although the cost of nanocolloids has been decreasing over time, it remains relatively high. The cost of new radiotracers is a major disadvantage of these, considering that the gain in detection rate is not much higher than that obtained with radiocolloids [ 71 ].…”
Section: Advantages and Disadvantages Of Nuclear And Non-nuclear Methodsmentioning
confidence: 99%
“…Twenty-two patients with BCa underwent [ 18 F]FDG PET/MRI, and as the MRI alone was scored by a radiologist for the probability of tumour in three locations (urinary bladder, pelvic lymph node or nonnodal pelvis), the nuclear medicine physician read the images of the fused PET/MRI [18]. The results showed that the addition of PET/MRI was superior for the determination of tumour in the lymph nodes with an accuracy of 95 versus 76% MRI alone [19 entities can be measured with fibroblast-activation protein inhibitor (FAPI), a quinolone-based tracer that acts as a fibroblast-activation protein inhibitor labelled with PET radionuclides. FAPI is a superior tracer compared with [ 18 F]FDG due to its higher uptake in the primary site as shown in a study comparing eighty patients with 28 different histopathologically proven tumour entities [21].…”
Section: F]fdg Pet/mrimentioning
confidence: 99%
“…Twenty-two patients with BCa underwent [ 18 F]FDG PET/MRI, and as the MRI alone was scored by a radiologist for the probability of tumour in three locations (urinary bladder, pelvic lymph node or nonnodal pelvis), the nuclear medicine physician read the images of the fused PET/MRI [18]. The results showed that the addition of PET/MRI was superior for the determination of tumour in the lymph nodes with an accuracy of 95 versus 76% MRI alone [19 ▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of imaging in treating lymphedema has benefited from new techniques in the area of lymphatic vessel anatomization, as demonstrated by the use of MRL in the pre-operative setting; similarly, ICG lymphography has demonstrated its ability to precisely identify lymphatic vessels to be subjected to reconstructive surgery in real time. Nuclear medicine has shown great potential in adding pathophysiological data to anatomical imaging [47][48][49][50][51]. These advancements are of value in many clinical scenarios where scintigraphy guides the treatment, as demonstrated by radioguided surgery (RGS) [52,53].…”
Section: The Role Of Imaging In the Prevention And Treatment Of Lymph...mentioning
confidence: 99%